2021
DOI: 10.38125/oajbs.000264
|View full text |Cite
|
Sign up to set email alerts
|

"Exploring the synergistic effect of Celery and Chinese kale on Antioxidant and Anti-Pancreatic Lipase and Anti-Acetylcholinesterase activities"

Abstract: It has been well known that vegetables provided numerous health benefits and mixed recipe derived local vegetables have been used in traditional folklore. Therefore, this study aimed to observe the synergistic effect of the mixed water extract of Celery and Chinese kale on chemical compositions using GC-MS analysis and the biological activity including antioxidant activity and inhibited acetylcholinesterase (AChE) and suppressed pancreatic lipase by in vitro study. The GC-MS analysis of the chemical compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In combination-1, several compounds that appear in A. cepa were also seen in combination-1 and insigni cant compounds in A. cepa were not detected in combination-1, such as ribofuranose, isoleucine, phenylalanine, gluconic acid, and 2,3,4-trihydroxybutyric acid. In addition, several different compounds from A. cepa appeared in combination-1, which might have come from A. graveolens L., which has been previously reported in A. graveolens L., including 2,3-butanediol 34 , mannitol, alanine, asparagine 41 , galactitol 53 , and 9,12octadecadienoic acid 40 . A synergistic combination of the compounds promoted the higher bioactivity of the GLVs.…”
Section: Gc-msmentioning
confidence: 52%
See 2 more Smart Citations
“…In combination-1, several compounds that appear in A. cepa were also seen in combination-1 and insigni cant compounds in A. cepa were not detected in combination-1, such as ribofuranose, isoleucine, phenylalanine, gluconic acid, and 2,3,4-trihydroxybutyric acid. In addition, several different compounds from A. cepa appeared in combination-1, which might have come from A. graveolens L., which has been previously reported in A. graveolens L., including 2,3-butanediol 34 , mannitol, alanine, asparagine 41 , galactitol 53 , and 9,12octadecadienoic acid 40 . A synergistic combination of the compounds promoted the higher bioactivity of the GLVs.…”
Section: Gc-msmentioning
confidence: 52%
“…The subsequent increase in activity was seen for LPI, with a moderate increase in activity (p < 0.05); the highest activity was from combination-7 (43.06%). Similarly, Khongrum, et al 34 reported that the combination of celery and Chinese kale extract showed more signi cant LPI activity (IC 50 0.048 mg/mL).…”
Section: Synergistic Combination Effectmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on Figure 3B it can be seen that the total phenol has decreased due to the longer drying time. [15] The longer drying process is being done, the phenolic compounds can be damaged. The drying process make the phenolic compounds oxidationed caused heat treatment which can damage the phenolic compounds.…”
Section: Total Phenolmentioning
confidence: 99%
“…In addition, the heating process during drying process also affects the total phenolic, because phenolic compounds are easily oxidized with over heat. So if the drying time is longer, the total phenolic will be decreased [15].…”
Section: Total Phenolmentioning
confidence: 99%